2021
DOI: 10.1002/bkcs.12409
|View full text |Cite
|
Sign up to set email alerts
|

Selective coordination of cobalt ions by zinc fingers in Escherichia coli

Abstract: The ability of peptides to coordinate with specific metal ions is crucial for environmental protection and recycling processes, because of the toxicity and scarcity of the ions. One-third of proteins in biological systems have binding affinities to specific metal ions, and thus, can be further applied to collect precious metal ions. Zinc ion is a necessary co-factor for the regulation of physiological responses in biological systems, because of its ability to bind biomolecules. In this study, three zinc finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…573 and 643 nm corresponding to d–d transitions were monitored, similar to those from the classical ZF domains, such as zinc interacting factor-268 (ZIF268) . Thus, the d–d Abs patterns observed in the Co­(II)–PARIS­(ZF2–4) complex suggest that the Co­(II) center is surrounded by PARIS­(ZF2–4), imparting a tetrahedral geometry that is typically detected in classical ZF domains. , …”
mentioning
confidence: 65%
See 4 more Smart Citations
“…573 and 643 nm corresponding to d–d transitions were monitored, similar to those from the classical ZF domains, such as zinc interacting factor-268 (ZIF268) . Thus, the d–d Abs patterns observed in the Co­(II)–PARIS­(ZF2–4) complex suggest that the Co­(II) center is surrounded by PARIS­(ZF2–4), imparting a tetrahedral geometry that is typically detected in classical ZF domains. , …”
mentioning
confidence: 65%
“…Curve-fitting based on the d–d transition suggested that the K d of Co­(II) from apo-PARIS­(ZF2–4) was (49.1 ± 7.7) × 10 –9 M (Figure A). This value varies from those of the other ZF domains because the general K d value is in the micromolar range. ,, This phenomenon can be explained by the effect of Co­(II) substitution in E. coli . After the addition of 100 μM cobalt, the E. coli expressed PARIS­(ZF2–4) coordinated with Co­(II), and this outcome was not detected in the case of other metal ions, including Cu­(II) and Fe­(III).…”
mentioning
confidence: 93%
See 3 more Smart Citations